Combined reactive/non-reactive DC magnetron sputtering of high temperature composite AlN–TiB2–TiSi2. (15th March 2016) - Pshyk, A.V.; Coy, L.E.; Yate, L.; Załęski, K.; Nowaczyk, G.; Pogrebnjak, A.D.; Jurga, S.
Abstract: High temperature composite target AlN–TiB2 –TiSi2 with heterogeneous distribution of compounds (AlN—50 wt.%; TiB2 —35 wt.%; TiSi2 —15 wt.%) is used for sputtering via combined reactive/non-reactive DC magnetron sputtering onto substrate materials either cylindrical polished steel (Fe, 18%—Ni, 12%—Cr, 10%—Ti) 3 mm diameter or monocrystalline silicon. The gradient coating has been produced by sequential non-reactive and reactive sputtering of the target. The structural and morphological properties of the deposited films are analyzed by transmission electron microscopy, scanning electron microscopy, atomic force microscopy, X-ray photoelectron spectroscopy and Raman spectroscopy. The tribo-mechanical properties are studied by means of nanoindentation and nanowear tests. The gradient film is composed of two layers with different microstructure and elemental composition. The first layer with thickness 200 nm is mainly based on light B, C and N as well metal elements Al, Si and Ti. The presence of very well distributed nanocrystals embedded in an amorphous matrix, with crystal sizes ranging from 5 to 40 nm is observed in the second layer 700 nm thickness and composed of Al, Ti, Si, B, and N. Films show very flat surfaces, with roughness around 0.35 nm. The hardness, elastic modulus, elastic recovery (We ), H/E ⁎ ratio and H 3 /E ⁎2 ratio are determined as 17.55 GPa, 216.7 GPa, 60%, 0.08 and 0.12 GPa, respectively. Nanowear tests demonstrate relatively high wear resistance of the coatings. Samples show promising characteristics for hard protective adaptive coatings and diffusion barriers due to short propagation of dislocations in the amorphous matrix and the elastic and hard nature of the nanocomposite structure. Graphical abstract: Highlights: Gradient two-layer nanocomposite coatings were synthesized using hybrid deposition method. New approach based on a combined non-reactive/reactive DC magnetron sputtering, from a composite target, was used. The structural, morphological and tribo-mechanical properties of the deposited coatings were analyzed. Samples show promising characteristics for hard protective adaptive coatings.